O1. The perturbation effect of titanium prosthesis on megavoltage radiotherapy beams: Photon versus electron beam measurements in a pelvic prosthesis phantom. (September 2016) - Ade, N.; du Plessis, F.
Abstract : Introduction: In some clinical situations involving external beam radiotherapy of malignancies in the hip region, patients may have metallic implants that could alter the absorbed dose distribution to the target and to normal tissue in the vicinity of the implant. This study investigates and compares the magnitudes of 10 × 10 cm 2 photon (6 and 15 MV) and electron (18 and 22 MeV) beam dose perturbations caused by unilateral titanium prosthesis. Materials and methods: Dose perturbations were measured and compared using dose maps and depth dose curves. Measurements were made with Gafchromic EBT2 films in a pelvic phantom made out of nylon slices. Transmission measurements were acquired in narrow beam geometry to determine the mass attenuation coefficient of nylon = 0.0443 cm 2 /g and for water-equivalent RW3 phantom material it was 0.0465 cm 2 /g. The magnitudes of dose deviation caused by the prosthesis were quantified by dose perturbation factors (DPFs), defined as the ratio of the dose influenced by the prosthesis and the unaltered beam. Results: For the 6 and 15 MV photons, maximum dose enhancements of 26.5 ± 1.0% and 29.0 ± 1.3%, and dose reductions of 19.9 ± 1.2% and 17.7 ± 1.1% were observed at the proximal interface and in the distal region of the prosthesis, respectively. For the 18 and 22 MeV electron beams respectively, maximum dose escalations of 17.4 ± 0.6% and 20.2 ± 0.7% were obtained at the proximal interface. A local hot spot of about 10% was however observed in the distal region of the prosthesis for the 22 MeV electrons. For the studied beams, the DPFs on the proximal side of the prosthesis fall off rapidly with distance from the proximal interface. Conclusion: The dose enhancement increases with increase in beam energy, with higher magnitudes obtained for the photon energies for the field size studied. The photon dose attenuation decreases with increase in photon energy.